Pengaruh Pendidikan Kesehatan berbasis Media Audiovisual pada Pengetahuan Anak-anak tentang Tuberkulosis - Lorenna, May (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Tuberculosis (TB) continues to be a global health concern. TB does not only harm adults, but also children. Therapy of TB in children is still found to fail, namely: incorrect treatment, treatment failure, and discontinuation of treatment so that appropriate education is required. This study aims to determine the impact of audiovisual media-based health education on children’s knowledge of tuberculosis. This study is a pre-experiment with one group pre-test post-test design. The population in this study was 60 students. Data were analyzed using the paired t-test statistical test. The results showed that there was a significant difference between before and after being given audiovisual media-based health education (p-value = 0.001). The number of respondents who had good knowledge before the intervention was 23 people (38.3%) increasing to 58 people (96.7%) after the intervention, while respondents who had sufficient knowledge before the intervention were 33 people (55%) decreasing to 2 people (3.3%) after the intervention. No respondents were included in the category of lacking knowledge after the intervention. These results indicate that health education with audiovisual media has an impact on children’s knowledge of tuberculosis. It is suggested that providing education about TB in children using audiovisual media should be done continuously to raise awareness of the threat of tuberculosis.